Tác động của tỉ lệ monome (ANi/o-Tol) đến một số tính chất của nanocompozit copolyme (ANi/o-Tol)/Fe2O3 nano - An, Trần Văn; Quế, Lê Xuân; Vỹ, Uông Văn (Vietnam Journal of Chemistry, 2015)
Nano composites PANi/POT/Fe2O3 synthesized by electrochemical method on 316 stainless steel in sulfuric acid solution  0.5 M,  with diferent wt-ratios aniline/o-toluidines: 10/0, 9/1, 8/2, 7/3, 6/4, nanoscale Fe2O3 2 % by weight of monomers, scan rate of the CV is 50 mV/s, step 5 mV and from -0.2 V to 1 V (SCE). PANi/POT/Fe2O3 was filtered, washed with distilled water to pH 7 then dried. Some principal properties of the nanocomposite were studied using CV technique, infrared spectroscopy (IR), thermal analysis (TGA), scanning electron microscopy (SEM) and tranmition electron microscopy (TEM). With increasing the ratio of o-Tol, the oxidation potential of the copolymer was increased and however the reduction potential was decreased. The presence of Fe2O3 provides a higher conductivity of the obtained nanocomposites.